2011
DOI: 10.1590/s0034-737x2011000300010
|View full text |Cite
|
Sign up to set email alerts
|

Populações de plantas na cultura da soja em cultivares convencionais e Roundup ReadyTM

Abstract: Este trabalho teve como objetivo estudar o comportamento de cultivares de soja convencionais e Roundup ReadyTM (RR) quando cultivados com diferentes populações de plantas por hectare. Foram realizados três ensaios no município de Jari, RS: em novembro de 2004 e de 2005 e em janeiro de 2006 (semeadura após a época indicada). Os cultivares convencionais utilizados foram: CEP/CD 41, CD 201, FUNDACEP 39 e CD 205 e os Roundup ReadyTM AL72, NK Mágica 7.3 RR e A 6001 RG nas populações de 250, 400 e 550 mil plantas ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
1
13
0
3
Order By: Relevance
“…SOARES et al (2015), in research conducted in Minas Gerais, confirmed that there is an interaction between the densities of sowing and soybean cultivars and showed that the population of 300 thousand plants per hectare is the most suitable for cultivation in the evaluated sites. Results obtained by LUDWIG et al (2011) also corroborate the existence of cultivars x population interaction. Evaluating different soybean cultivars in three plant populations (250, 400 and 550 thousand plants ha -1 ), the authors obtained better results for the population of 550 thousand plants ha -1 .…”
Section: Introductionsupporting
confidence: 69%
“…SOARES et al (2015), in research conducted in Minas Gerais, confirmed that there is an interaction between the densities of sowing and soybean cultivars and showed that the population of 300 thousand plants per hectare is the most suitable for cultivation in the evaluated sites. Results obtained by LUDWIG et al (2011) also corroborate the existence of cultivars x population interaction. Evaluating different soybean cultivars in three plant populations (250, 400 and 550 thousand plants ha -1 ), the authors obtained better results for the population of 550 thousand plants ha -1 .…”
Section: Introductionsupporting
confidence: 69%
“…Important information on crop treatments for the arrowroot production includes the plant population, which aims to maintain or increase crop yield (Terra et al 2010) and may be adjusted by changing the spacing between rows and increasing plant density along the rows according to an ideal population, since intrinsic genotype traits and environmental conditions may interfere in the results (Ludwig et al 2011).…”
Section: Abstract Resumomentioning
confidence: 99%
“…In Brazil, many studies have been conducted to adjust the density of soybean plants in order to increase grain yield (Ludwig et al, 2011;Balbinot Júnior et al, 2015;Silva et al, 2015). However, there are few studies considering cultivars with indeterminate growth habit, development cycle shorter than 120 days and plants with low size and compact architecture -attributes increasingly desired in soybean genetic breeding programs (Souza et al, 2010).…”
Section: Introductionmentioning
confidence: 99%